Emergency remote teaching due to COVID-19 pandemic and potential risks for socioeconomically disadvantaged students in higher education - Turgut Karakose (ÜNİVERSİTEPARK Limited, 2021)
Background/purpose - Higher education institutions worldwide rapidly switched to emergency remote teaching with a sustainable quality education approach in response to the global health threat caused by the COVID-19 virus. The sudden and largely unprepared transition to emergency remote teaching placed serious pressures on not only students, but also academics, the families of both, and also other stakeholders as well. This study aims to discuss the potential effects of emergency remote teaching due to COVID-19 on disadvantaged students in higher education. Materials/methods - This study is a review article, which presents a brief literature review on the potential impact of emergency remote teaching due to COVID-19 on disadvantaged students in higher education. Practical implications - This study may help to provide researchers and practitioners with a roadmap for potential future work on the impact of emergency remote teaching in response to the COVID-19 pandemic on disadvantaged groups. From this perspective, the potential effect of emergency remote teaching on disadvantaged students in higher education is examined and recommendations put forwards for solutions aimed at educational administrators and decision-makers. Conclusion - The emergency remote teaching put in place due to the COVID-19 pandemic has led to the widening of the digital divide among higher education students. Therefore, integrating the digital and distance education approach into the higher education system correctly and effectively may both facilitate the achievement of instructional goals and also help to eliminate digital inequality in the higher education student population.